The child with spontaneous recurrent bleeding in the eye - Rao, Aparna (BMJ Publishing Group, 2014)
Juvenile xanthogranuloma is a self-limiting dermatological condition characterised by spontaneous hyphaema due to uveal involvement causing neovascularisation. Recurrent hyphaema in a child should alert the clinician towards this rare diagnosis. Appropriate investigations and treatment should be directed towards treating this possible diagnosis associated with neovascular glaucoma where routine filtering surgeries may be associated with several complications.